2021
DOI: 10.1002/jcop.22708
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between problematic Internet use in adolescents and emotion regulation difficulty and family Internet attitude

Abstract: The study aims to determine the relationship between problematic Internet use in adolescents and emotion regulation difficulty and family Internet attitude. The study used a descriptive and correlational design. The sample of the study consisted of 5916 students. The data were collected using the “Problematic Internet Use Scale,” “Difficulties in Emotion Regulation Scale,” “Internet Parental Style Scale.” The total score on the Problematic Internet Use Scale was 55.41 ± 19.60 while the total score on the Diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…While not a primary consideration for this survey, comparisons of parenting style demonstrated some correlation with high IAT scores in young people. These data warrant further investigation but support earlier literature suggesting the association of parental mental health, parenting style, and familial demographics with development of PIU.…”
Section: Discussionsupporting
confidence: 81%
“…While not a primary consideration for this survey, comparisons of parenting style demonstrated some correlation with high IAT scores in young people. These data warrant further investigation but support earlier literature suggesting the association of parental mental health, parenting style, and familial demographics with development of PIU.…”
Section: Discussionsupporting
confidence: 81%
“…Among the included articles, there was a significant positive correlation between adolescents' DERS total scores and their severity of problematic smartphone use ( Amendola, Spensieri, Guidetti, & Cerutti, 2019 ; Coco et al., 2020 ; Domoff, Sutherland, Yokum, & Gearhardt, 2020 ; Giordano, Coco, Salemo, & Biasi, 2020 ; Mancinelli, Sharka, Lai, Sgaravatti, & Salcuni, 2021 ) and problematic Internet use ( Amendola et al., 2019 ; Anita, András, & Bernadette, 2014 ; Casale et al., 2016 ; Estévez, Jáuregui, Sánchez-Marcos, López-González, & Griffiths, 2017 ; Faghani, Akbari, Hasani, & Marino, 2019 ; Gutiérrez, Fernández, Gonzalvo, & Bilbao, 2014 ; Günaydın, Arıcı, Kutlu, & Demir, 2021 ; Kafali et al., 2020 ; Kim & Chun, 2016 ; Love, May, Shafer, Fincham, & Cui, 2022 ; Mo, Chan, Chan, & Lau, 2018 ; Qi, 2019 ; Sertbaş et al., 2020 ; Uçur & Dönmez, 2021 ; Wang & Qi, 2017 ; Yorulmaz, Civgin, & Yorulmaz, 2020 ). The DERS was developed by Gratz and Roemer (2004) to measure emotion dysregulation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that internet activities are closely related to mental states and emotional signs (Gros et al, 2020). This is supported by Günaydın et al (2021), whose findings showed that one of the factors that can influence problematic internet use is emotion regulation difficulties. Maladaptive emotion regulation is a factor that can sustain problematic internet use in individuals (Wartberg and Linderberg, 2020).…”
Section: Introductionmentioning
confidence: 79%